(untitled) - Castellan, Gilbert William (Reading, Mass., 1983)
Contents: Some fundamental chemical concepts; Empirical properties of gases; Real gases; The structure of gases; Some properties of liquids and solids...
Hóa lý 1
Keywords: Chemistry, physical and theoretical,Hóa học, vật lý và lý thuyết